Environmental asbestos disease: Pleural plaque volume measurement with Chest Tomography is there a correlation between pulmonary function? - Çoşğun, Ibrahim Güven; Evyapan, Fatma; Karabulut, Nevzat (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Objectives: Chest X-ray is correlated with pulmonary function of asbestos related disease. These correlations limited by low specific and sensitive. Computed tomography (CT) more sensitive. There was no adopted for the measurement of CT. Our aim in this study, to determine between correlation pleural plaque (PP) volume and lung function for use improving classification with CT. Methods: The study included 75 patients with environmental asbestos exposure. PP areas measured in patients were divided by the patient lung area to determine PP ratio with CT. Diffusing capacity and six minute walking distance (6MWD) measured and evaluated quality of life. Results: PP identified in 66 (88%) of the patients with CT. PP most frequently noted in the front right quadrant and had an average plaque volume of 7729,17 mm3. Plaque ratio taken as the percentage of the ratio to the lung volume, mean plaque percentage was 0,37±0,45% (0,003-2,3). In 12(18,1%) of the patients, asbestosis not seen with chest X-ray was detected with CT. Conclusions: PP volume and ratios were not statistically significantly correlated with respiratory functions, exercise capacity, cumulative amount of exposure. Patient of asbestos disease total lung capacity was lower, 6MWD distance was shorter and quality of life was poorer.